2014
DOI: 10.1007/s10266-014-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-mangostin suppresses IL-6 and IL-8 expression in P. gingivalis LPS-stimulated human gingival fibroblasts

Abstract: This study aims to investigate the effect of alpha-mangostin on interleukin (IL)-6 and IL-8 expression in human gingival fibroblasts (HGFs). HGFs were challenged with Porphyromonas gingivalis LPS and then treated with various concentrations of alpha-mangostin. The cytotoxicity was determined using MTS assay and cytokine expressions were evaluated by Real-time PCR and ELISA. The results showed that 5 μg/ml P. gingivalis LPS and alpha-mangostin at 1 µg/ml or less did not affect the viability of HGFs. Alpha-mango… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…5 Stimulation of gingival fibroblasts by LPS induces the activation of nuclear factor kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) pathways, which finally results in the release of cytokines, such as tumour necrosis factor alpha (TNF-a), interleukin (IL)-6, and IL-8. 6,7 These inflammatory mediators induce the destruction of connective tissue, and they play important roles in the development of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…5 Stimulation of gingival fibroblasts by LPS induces the activation of nuclear factor kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) pathways, which finally results in the release of cytokines, such as tumour necrosis factor alpha (TNF-a), interleukin (IL)-6, and IL-8. 6,7 These inflammatory mediators induce the destruction of connective tissue, and they play important roles in the development of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study demonstrating in vivo effect of α-MG on IL-6 production, although a previous in vitro study showed that α-MG suppresses IL-6 and IL-8 expression in LPS-stimulated human gingival fibroblasts (Yiemwattana and Kaomongkolgit, 2015). IL-6, a pro-inflammatory cytokine which is released after peripheral immune challenge, has been shown to bind to its receptor on brain endothelial cells and to increase COX-2 expression and prostaglandin synthesis (Eskilsson et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…An in vitro study [107] revealed that α-MG suppresses IL-6 and IL-8 secretion in LPS-triggered human gingival fibroblasts. Nevertheless, studies [101,108] have proven that IL-6, which was secreted after peripheral immune experimentation, binds to its receptor on brain endothelial cells resulting in upsurge of COX-2 secretion as well as prostaglandin synthesis.…”
Section: Neuroinflammatory Potentails Of α-Mgmentioning
confidence: 99%